Synthesis of meso‐Free Decaphyrin(1.1.1.1.1.1.1.1.1.1) by a Hydrodebromination Protocol; Aromaticity and Solvent‐Polarity Dependent Conformational Change. Issue 68 (10th October 2022) - Nakai, Akito; Saito, Hayate; Yorimitsu, Hideki; Tanaka, Takayuki; Osuka, Atsuhiro
Abstract: A meso ‐free β ‐bromodecaphyrin has been constructed by [2+3+2+3] type acid‐catalyzed cross‐condensation and subsequent oxidation. Hydrodebromination of this tetrabromodecaphyrin with NaBH4 in the presence of TMEDA and palladium catalyst afforded β ‐unsubstituted doubly meso ‐free [46]decaphyrin(1.1.1.1.1.1.1.1.1.1) as the first example of β ‐unsubstituted meso ‐free regular expanded porphyrins with the number of pyrrole units larger than eight. It exhibits distinct aromaticity originating from its 46π‐conjugated electronic circuit and flexible conformational change between non‐twisted and doubly twisted forms depending on the solvent‐polarity. Their distinct conformations have been analyzed by combined experimental and theoretical investigations. Abstract : A meso ‐free β ‐bromodecaphyrin has been constructed by [2+3+2+3] type acid‐catalyzed cross‐condensation and subsequent oxidation. Hydrodebromination of this tetrabromodecaphyrin afforded β ‐unsubstituted doubly meso ‐free [46]decaphyrin(1.1.1.1.1.1.1.1.1.1), exhibiting distinct aromaticity originating from its 46π conjugation circuit and flexible solvent‐polarity dependent conformational change between non‐twisted and doubly twisted forms.